Project on Human Development in Chicago Neighborhoods (PHDCN): Wechsler Adult Intelligence Scale-Revised, Wave 2, 1997-2000 - Earls, Felton J. ([Verlag nicht ermittelbar], 2006)
The Project on Human Development in Chicago Neighborhoods (PHDCN) was a large-scale, interdisciplinary study of how families, schools, and neighborhoods affect child and adolescent development. One component of the PHDCN was the Longitudinal Cohort Study, which was a series of coordinated longitudinal studies that followed over 6,000 randomly selected children, adolescents, and young adults, and their primary caregivers over time to examine the changing circumstances of their lives, as well as the personal characteristics, that might lead them toward or away from a variety of antisocial behaviors. Numerous measures were administered to respondents to gauge various aspects of human development, including individual differences, as well as family, peer, and school influences. The Wechsler Adult Intelligence Scale-Revised (WAIS-R) was a general test of intelligence, which David Wechsler, the test's author, defined as "the global capacity of the individual to act purposefully, to think rationally, and to deal effectively with his environment." In keeping with this definition of intelligence as an aggregate of mental aptitudes or abilities, the WAIS-R has traditionally consisted of 11 subtests divided into two parts, verbal and performance. For this study, the WAIS-R included definitions of words only. It was only administered to Cohort 18.